Analisis Manajemen Operasional Terhadap Strategi Distribusi dan Pengaruhnya Terhadap Peningkatan Penjualan - Anwar Sanusi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Operational management is an important part of problem solving factors in manufacturing companies because they have to face changing environmental conditions. Marketing Strategy is a strategy designed to promote goods or services with the aim of generating profits. Especially in some contexts, consumers tend to focus more on brands than products when making purchases, choosing certain brands because they have a positive image. Qualitative research methods place more emphasis on observing phenomena that occur and more on examining the substance of the meaning of these phenomena. Descriptive qualitative research means that the researcher must describe an object, phenomenon, or social setting which will be outlined in narrative writing. Benefits and Objectives of Company Operational Management 1. Efficiency (increasing efficiency) 2. Productivity (increasing efficiency) 3. Economy (reducing costs) 4. Quality (improving quality) 5. Reduced processing time (reducing production process time) Suggestions for this research are that several objects can be added to determine product quality improvements.